2014
DOI: 10.1002/oby.20739
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 1‐year exercise and lifestyle intervention on irisin, adipokines, and inflammatory markers in obese children

Abstract: Objective: Exercise improves weight status and metabolism. Irisin, a novel myokine, may be involved in the regulation of metabolic function. The effect of an exercise and dietary lifestyle intervention for 1-year on irisin, adipokines (leptin, adiponectin, resistin) and inflammatory markers (C-reactive protein (CRP), soluble tumor necrosis factor receptor II (sTNFR-II) was evaluated, and predictors of irisin levels were characterized in obese children. Methods: Parameters were assessed at baseline and at follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
5
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 39 publications
10
97
5
7
Order By: Relevance
“…Adopting aerobic exercise for 3-months significantly induced irisin levels in both control and obese groups. Our results corroborated with those of Boström et al 5 and Bluher et al 44 who reported increased irisin levels after 10 weeks and 1 year of physical exercise, respectively. The exerciseinduced irisin levels in our studies were significantly correlated with improved cognitive functions after controlling for confounding factors that could affect cognitive process.…”
Section: 35supporting
confidence: 93%
“…Adopting aerobic exercise for 3-months significantly induced irisin levels in both control and obese groups. Our results corroborated with those of Boström et al 5 and Bluher et al 44 who reported increased irisin levels after 10 weeks and 1 year of physical exercise, respectively. The exerciseinduced irisin levels in our studies were significantly correlated with improved cognitive functions after controlling for confounding factors that could affect cognitive process.…”
Section: 35supporting
confidence: 93%
“…By contrast, other authors did not find any correlation between adiponectin and leptin [10,14,96] in OW and OB children, despite the association of both adipokines with IR and adiposity.…”
Section: Adiponectin and Markers Of Inflammationmentioning
confidence: 65%
“…In children, HMW adiponectin multimer is usually linked to an improvement in insulin resistance (IR) and lipid profile [6], and it has been negatively associated with cardiometabolic complications [8]. The negative associations of HMW adiponectin with IR and adiposity appear to be present even in pre-pubertal (PP) individuals [9,10]. Zimmet et al reported that in PP children, HMW adiponectin was negatively associated with body mass index (BMI) z-score, IR, triglycerides (TG), leptin and soluble intracellular adhesion molecule (sICAM); however, after adjustment for age and sex, only BMI z-score and TG maintained their negative association with HMW adiponectin [11].…”
Section: Adiponectin and Its Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an RCT study, Balagopal et al (2010) found a reduction in leptin and increase in soluble leptin receptor in obese children after a 3-month lifestyle intervention (physical activity, caloric restriction and limiting TV time). In an intervention study in obese children, Bluher et al (2014) found that leptin decreased after a one-year lifestyle intervention (physical activity and educational classes for parents) compared with baseline. In the current study, we did not find intervention effects on leptin at 52-week follow-up.…”
Section: Discussionmentioning
confidence: 99%